Self-Medication Behaviour in Indian Patients: A Quantitative Study - KHAN, AHMED NAWAZ (International Journal of Psychosocial Rehabilitation, 2018)
In India, patients frequently buy and take pharmaceuticals without a prescription or medical supervision, which is known as self-medication. Due to the potential for harmful health effects such drug resistance and toxicity, this behaviour has grown to be a source of concern. The lack of access to healthcare, the high cost of medical care, and the cultural conviction that traditional remedies work among Indian patients are only a few of the factors that contribute to self- medication. According to studies, those with lower incomes and educational levels are more likely to self-medicate. Due to the extensive availability of unregulated pharmaceuticals and the simplicity with which over-the-counter medications may be obtained in India, self- medication is becoming more and more common. To address this problem, there is a need for greater knowledge of the dangers of self-medication and the significance of getting medical help. To encourage responsible medication, use and make sure that patients have access to safe and effective treatment alternatives, healthcare professionals, lawmakers, and the pharmaceutical industry can all play a significant role.